Effects of Flipped Classroom Approach on Health Assessment Knowledge and Skills Among Undergraduate Nursing Students (Medical Forum Monthly, 2023)
Effects of Flipped Classroom Approach on Health Assessment Knowledge and Skills Among Undergraduate Nursing Students